Balancing work and life: Social media’s mediating role in enhancing employee performance - Rosaly Franksiska; Ahyar Yuniawan (Diponegoro International Journal of Business, 2025)
This study investigates the relationship between work-life balance, social media usage, and employee performance, focusing on social media's mediation role. Drawing on Boundary Theory, which studies the blurring of work and personal boundaries, the study looks at how social media can help or hinder employee performance in the context of work-life balance. Data were gathered and analyzed to evaluate four hypotheses: Work-life balance improves employee performance; Work-life balance boosts social media usage; Social media usage improves employee performance; and Social media usage mediates the link between worklife balance and employee performance. The data confirm that work-life balance has a favorable relationship with both social media usage and employee performance, with social media acting as an effective mediator. These findings underscore social media's dual role as a productivity tool and facilitator of work-life balance. The study adds to the expanding corpus of research on digital technologies in the workplace, recommending that firms use social media to improve employee well-being and performance. Future research should look into the potential obstacles and long-term repercussions of social media use in various job settings.